Verdir les zones sèches agrosylvopastorales marginales au Moyen- Orient, en Afrique du Nord et dans la Corne de l’Afrique - Strohmeier, Stefan; Haddad, Mira; Louhaichi, Mounir (Agropolis International, 2022)
A chapter in Agroecology Transformation for Sustainable Food Systems: Insight on FRANCE-CGIAR Research. This chapter is about greening marginal agrosylvopastoral drylands in the Middle East. ICARDA, in collaboration with international and national partners and target dryland communities, developed agrosylvopastoral watershed rehabilitation and sustainable management packages that capitalize on the upsides of the overall threatening conditions to foster agroecological transition.